Bonding Characteristics of Sn-57Bi-1Ag Low-Temperature Lead-Free Solder to Gold-Plated Copper. (2017) - Maruya, Yuki; Hata, Hanae; Shohji, Ikuo; Koyama, Shinji
Abstract: To fabricate a higher melting point joint by bonding at a low temperature, bonding characteristics of Au/Cu joints bonded at various bonding conditions using Sn-57Bi-1Ag solder were investigated. They were compared with those of the Cu/Cu joint. In the Au/Cu joint bonded at 170 o C for 1 min, a large scallop-shaped AuSn4 layer formed in the joint interface of Au and solder. A Au-diffused layer formed in the tip of the AuSn4 layer. The Sn-Cu-Au layer including approximately 20 mol% Au formed in the joint interface of Cu and solder. With increasing the bonding time, both the eutectic microstructure with β-Sn and Bi and the Au layer disappeared. As the result, the solder area changed from the eutectic microstructure to Bi phases including AuSn4 and Ag3 Sn phases in the bonding time over 30 min. In contrast, the eutectic microstructure formed in the Cu/Cu joint bonded at 170 o C regardless of the bonding time. The bond strength of the Au/Cu joint was approximately one-third of that of the Cu/Cu joint. In both joints, the bond strength reduced with increasing the bonding time due to the fracture mode change.